Incurred sample reanalysis in drug discovery bioanalysis. (6th December 2018) - Giri, Poonam; Patel, Nirmal; Joshi, Vipul; Giri, Shyamkumar; Srinivas, Nuggehally R.
Abstract: Bioanalysis plays a key role during the drug discovery process to generate the pharmacokinetic data to facilitate unbiased evaluation of leads, optimized leads and drug candidates. Such pharmacokinetic data are used to enable key decisions in the drug discovery process. The aim of the work is to put forward a new strategy of performing the incurred sample reanalysis for select small molecule novel chemical entities at different stages of drug discovery prior to candidate selection. Three discovery programs representing hits, leads and optimized lead candidates were selected for the incurred sample reanalysis (ISR) analysis. From each discovery program, two novel chemical entities were selected for the ISR analysis. The time points considered for ISR generally varied among the programs; however, samples coinciding with drug absorption, distribution and elimination were considered in the ISR assessment. With the exception of a single ISR value that gave a high deviation (about 63%), the observed ISR values supported the discovery bioanalytical assays. While the individual bioanalytical laboratory can draw an algorithm for selecting novel chemical entities and fixing the acceptance criteria for the ISR data, it is proposed that the percentage difference between ISR vs. original concentration for 67% of the repeat samples is contained within ±30% for discovery bioanalysis.